Model Pelayanan Keprotokolan Pada Masa Adaptasi Kebiasaan Baru di Provinsi Jawa Barat - Mas Adi Komar; Joni Dawud; Hendikus T Gedeona (Jurnal Media Administrasi Terapan, 2023)
The purpose of this study was to conduct an analysis of protocol services during  the  adaptation  period  to  new  habits,  which  then designed an information technology-based protocol service model in the local government of West Java province. The method used in this study uses a qualitative descriptive approach. Data collection techniques are carried out to obtain primary data and secondary data that interviews, observation, and documentation studies. Data analysis in this study uses a systems approach with a soft system methodology (SSM), with CATWOE analysis and role analysis. Based on the results of research using the concept/theory of service quality with its 5 aspects, the aspects that have been implemented well are the Reliability, Empathy, and Assurance aspects, what needs to be strengthened is the Responsiveness, Tangible aspects. There are obstacles in protocol services during the adaptation period to new habits in the Regional Government of West Java Province, namely the need to improve services in the response or attitude of the apparatus, limited human resources, the use of room facilitation data that is still manual. Development of a protocol service model during the adaptation period to new habits as a solution and innovation for the Regional Government in order to improve services in the Protocol Section in West Java Province. The recommendations for improving protocol services include: increasing the use of technology in the protocol service process, strengthening human resources through scheduled protocol training, supporting facility and infrastructure facilitation considering protocol services.